2020
DOI: 10.1186/s12939-020-01266-5
|View full text |Cite
|
Sign up to set email alerts
|

Do community scorecards improve utilisation of health services in community clinics: experience from a rural area of Bangladesh

Abstract: Background The government of Bangladesh initiated community clinics (CC) to extend the reach of public health services and these facilities were planned to be run through community participation. However, utilisation of CC services is still very low. Evidence indicates community score card is an effective tool to increase utilisation of services from health facility through regular interface meeting between service providers and beneficiary. We investigated whether community scorecards (CSC) improve utilisatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
5
5
0
Order By: Relevance
“…While our previous findings align with some earlier studies like GoB (2019) and Hanifi et al (2020), they seem to oppose the stated preference for nearby health centres. In particular, when asked whether distance to health facilities is a problem, around 43% of respondents in the 2017 round of BDHS have reported 'big problem' against the option 'not a big problem/no problem'.…”
Section: Resultssupporting
confidence: 88%
“…While our previous findings align with some earlier studies like GoB (2019) and Hanifi et al (2020), they seem to oppose the stated preference for nearby health centres. In particular, when asked whether distance to health facilities is a problem, around 43% of respondents in the 2017 round of BDHS have reported 'big problem' against the option 'not a big problem/no problem'.…”
Section: Resultssupporting
confidence: 88%
“…The government of Bangladesh's flagship initiative, community clinics (CC), a unique public-private partnership run through community participation, were set up to extend the reach of primary health services to rural people at grassroot levels. Studies have shown that utilization of CC services is low and can be improved through strengthened community engagement using social accountability approaches (31). Results achieved in this study indicate that strengthening the existing community clinic set up, ensuring relevant and skilled human resources, and intensifying community engagement will not only boost service utilization of community clinics, but will also increase immunization coverage of children as well.…”
Section: Policy Implicationmentioning
confidence: 76%
“…However, our findings indicated that people living with NCDs expressed a low level of preference and willingness for using NCD services. The provision of healthcare services in CCs was focused more on managing family planning services, reproduction and child care, and basic health services, which might have influenced their preference and willingness [ 55 ]. The shortage of supplies and resources, including medicines and diagnostic facilities in CCs, UHCs, and Upazila Health Complex resulted in a lower preference for using NCD services, which is similarly reported in primary healthcare settings in several countries [ 56 59 ].…”
Section: Discussionmentioning
confidence: 99%